Sustainable Urban Farming: Budidaya Lalat Tentara Hitam (Hermetia illucens) untuk Menghasilkan Pupuk, dan Pakan Ikan dan Unggas - Siti Herlinda; Jelly Milinia Puspita Sari (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Herlinda S, Sari JMP. 2021. Sustainable Urban Farming: Cultivation of black soldier fly (Hermetia illucens) to produce manure, and fish and poultry feedstuff. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 27-37. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Urban farming in this pandemic era is a necessity for the community because in addition to entertainment, it can also increase income if it is done professionally. Manure and fish and poultry feedstuff can be produced by cultivating black soldier fly (BSF) or Hermetia illucens in the yard using municipal organic waste. This paper aimed to review and come up with ideas on how to cultivate BSF to produce the manure, and fish and poultry feedstuff. Cultivation of BSF was carried out using organic materials or municipal organic waste. BSF has life stages starting from egg, larvae, pupae, and adult stage or fly. In the adult stage, the fly lays eggs next to a food source or organic waste that has pungent smell, then the eggs hatched into larvae. The larvae consumed and decomposed the organic material waste or the municipal organic waste or livestock feces into a final product in the form of organic fertilizer or “kasgot” (=BSF manure). The BSF manure contained nutrients for plants, such as NPK elements. BSF larvae and pupae contained a lot of protein and could be directly used for poultry and fish feedstuff which had high selling value. BSF cultivation was also useful in overcoming the municipal organic waste problems, such as food waste, livestock feces, and other organic wastes. BSF cultivation did not require a large area for farming and could be carried out in the house yard so it was very suitable for urban farming. Thus, this BSF has the potential to be developed to producing the organic fertilizer, it can also produce the fish and poultry feedstuff.